Analysis of a long-duration AR throughout five solar rotations: Magnetic properties and ejective events - Iglesias, Francisco Andres (2019)
Coronal mass ejections (CMEs), which are among the most magnificent solar eruptions, are a major driver of space weather and can thus affect diverse human technologies. Different processes have been proposed to explain the initiation and release of CMEs from solar active regions (ARs), without reaching consensus on which is the predominant scenario, and thus rendering impossible to accurately predict when a CME is going to erupt from a given AR. To investigate AR magnetic properties that favor CMEs production, we employ multi-spacecraft data to analyze a long duration AR (NOAA 11089, 11100, 11106, 11112 and 11121) throughout its complete lifetime, spanning five Carrington rotations from July to November 2010. We use data from the Solar Dynamics Observatory to study the evolution of the AR magnetic properties during the five near-side passages, and a proxy to follow the magnetic flux changes when no magnetograms are available, i.e. during far-side transits. The ejectivity is studied by characterizing the angular widths, speeds and masses of 108 CMEs that we associated to the AR, when examining a 124-day period. Such an ejectivity tracking was possible thanks to the multi-viewpoint images provided by the Solar-Terrestrial Relations Observatory and Solar and Heliospheric Observatory in a quasi-quadrature configuration. We also inspected the X-ray flares registered by the GOES satellite and found 162 to be associated to the AR under study. Given the substantial number of ejections studied, we use a statistical approach instead of a single-event analysis. We found three well defined periods of very high CMEs activity and two periods with no mass ejections that are preceded or accompanied by characteristic changes in the AR magnetic flux, free magnetic energy and/or presence of electric currents. Our large sample of CMEs and long term study of a single AR, provide further evidence relating AR magnetic activity to CME and Flare production.